2009
DOI: 10.1088/0067-0049/181/2/473
|View full text |Cite
|
Sign up to set email alerts
|

Eta Carinae Across the 2003.5 Minimum: Analysis in the Visible and Near-Infrared Spectral Region

Abstract: We present an analysis of the visible through near-infrared spectrum of Eta Carinae (η Car) and its ejecta obtained during the "η Car Campaign with the Ultraviolet and Visual Echelle Spectrograph (UVES) at the ESO Very Large Telescope (VLT)." This is a part of larger effort to present a complete η Car spectrum, and extends the previously presented analyses with the Hubble Space Telescope/Space Telescope Imaging Spectrograph (HST/STIS) in the UV (1240-3159 Å) to 10,430 Å. The spectrum in the mid-and near-UV is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Studies of the STIS far‐UV and mid‐UV echelle spectra of η Car (Nielsen, Gull & Vieira Kober 2005) suggested a decline in highly excited atomic states beginning about 6 months before the X‐ray drop/spectroscopic minimum in 2003.5. Nielsen et al (2009) demonstrated that the major drop of the high‐ionization wind lines occurred with complementary growth of low‐ionization wind lines.…”
Section: The Spatially‐resolved Line Profilesmentioning
confidence: 94%
“…Studies of the STIS far‐UV and mid‐UV echelle spectra of η Car (Nielsen, Gull & Vieira Kober 2005) suggested a decline in highly excited atomic states beginning about 6 months before the X‐ray drop/spectroscopic minimum in 2003.5. Nielsen et al (2009) demonstrated that the major drop of the high‐ionization wind lines occurred with complementary growth of low‐ionization wind lines.…”
Section: The Spatially‐resolved Line Profilesmentioning
confidence: 94%
“…Column 9 of Table 1 lists other features that blend with the line of interest and that complicate measurements. More complete listings of line blends can be found in the tables of Nielsen et al (2009) and Zethson et al (2012). Brief descriptions of the observed properties and variations follow in subsections for each line species.…”
Section: Wind Line Morphologies During the 20090 Eventmentioning
confidence: 99%
“…The complication is in that it is not simple to estimate the population of the relevant atomic state. Nielsen et al (2009) present high spectral resolution (R ∼ 80, 000) of the hydrogen Hδ line, as well as of the He I λ7067Å line, across the 2003.5 spectroscopic event. The He I λ7067Å line shows Doppler shift variations with the orbital phase that fit emission and absorption in the acceleration zone of the secondary wind (Kashi & Soker 2007, 2008b.…”
Section: Appendices (Astro-ph Version Only) Appendix A: the Brief Abs...mentioning
confidence: 92%
“…This may suggest that part of the absorption in the Hδ line is from the conical shell, in addition to an absorption component associated with the primary wind. Close to periastron (phase 1.001 in figure 5 of Nielsen et al 2009) the Hδ line shows an anomalous wide blue absorption wing, reaching velocities up to −v ≃ 900 km s −1 . At the closest observation times, phases 0.985 and 1.115, this broad absorption does not exist.…”
Section: Appendices (Astro-ph Version Only) Appendix A: the Brief Abs...mentioning
confidence: 96%
See 1 more Smart Citation